Faktor-Faktor Yang Mempengaruh Nilai Perusahaan Pada Perusahaan Manufaktur Otomotif Periode 2016-2019 - Clarissa Fortuna, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
In this study, an analysis of the effect of tax planning and tax avoidance on firm value in automotive manufacturing companies listed on the IDX for the period 2016-2019 was conducted. The sample selection used purposive sampling with a panel data model with a total study of 13 companies. The study was conducted using the Statistical Package for the Social Sciences (SPSS) ver 25 and SmartPLS 3.3.2. The results showed that tax planning had a significant negative effect on firm value, while tax avoidance had no effect on firm value. This research shows that debt funding and firm size control variables have no effect on firm value. The implication of this research is that if companies do tax planning and tax avoidance that is too aggressive, it will be illegal and can lead to tax audits from the tax authorities. The value of the company will decrease because the company is deemed non-compliant with tax regulations.